Concerns of students from Malaysian Institutions of Higher Learning on the symbols of nationality as Malaysian identity - Mohamad, Ayu Nor Azilah; Haniffa, Mohamed Ali; Mohamad, Wayu Nor Asikin (Science and Engineering Research Support Society, 2020)
This article discusses the degree of which students of Institutions of Higher Learning (IPT) students care about the symbols of Malaysian nationality as Malaysian identities. These HEIs are composed of Public Institutions of Higher Learning (IPTA) and Private Institutions of Higher Learning (IPTS) located in Peninsular Malaysia only. These national symbols include the National Assembly, National Anthem, National Flag, National Flower and National Language. This article reports the quantitative analysis conducted using a set of questionnaire. A total of 150 respondents were involved in answering the questionnaire as a pilot study. The data were analyzed descriptively using SPSS version 24. Preliminary survey results found that the level of concern for students of the national symbols as a Malaysian identity was in good standing with an alpha value of 0.776. This finding is one of the benchmarks of the younger generation's spirit of patriotism towards Malaysia.